A brachypterous Bryophaenocladius (Diptera: Chironomidae: Orthocladiinae) with hypopygium inversum from Heggie’s Rock, Georgia, U.S.A. - Epler, J. H. (Zootaxa, 2012)
The adult male and female, pupa and larva of a new species, Bryophaenocladius chrissichuckorum, are described fromHeggie’s Rock, Georgia, U.S.A. Males and females of the species are brachypterous; males have a hypopygium inversum.Pupae differ from other described Bryophaenocladius by the presence of three pairs of small setae on the prefrons. Larvaehave a mentum with 2 broad median teeth and AR of about 0.99, but are not realistically separable from many other Bryophaenocladius species. The immature stages inhabit shallow ephemeral pools.